IMPACTS OF GEOMORPHIC DISTURBANCES ON PLANT COLONIZATION IN EBBA VALLEY, CENTRAL SPITSBERGEN, SVALBARD - Stawska, Monika (Quaestiones Geographicae, 2017)
Global warming observed nowadays causes an increase in geomorphic activity in polar regions. Within the areas influenced by cold climatic conditions, relief dynamics and vegetation development are the main landscape shaping processes. The study is limited to the Ebba Valley (78°43’N; 16°37’E) in central Spitsbergen (Svalbard), where geomorphologic observations and vegetation sampling were conducted in 2007. The valley was divided into three zones differentiated by dominating geomorphic activity and stability of deposits. The settlement and the evolution of plant cover have been documented there. The main factors that control well developed vegetation cover within raised marine terraces are frost heave and solifluction. In deeper parts of the valley, aeolian processes dominate and high differentiation of microsite conditions causes high variability in plant coverage. The area close to the Ebba glacier marginal zone is characterized by initial stages of plant colonisation where disturbance to vegetation is mainly caused by hydrological processes.